Influence of a protocol of Pilates exercises on the contractility of the pelvic floor muscles of non-institutionalized elderly persons - Souza,Ligia Muniz de (2017)
Abstract Objective: To investigate the influence of a protocol of Pilates exercises on the functionality and contractility of the pelvic floor muscles (PFM) of older women living in the city of Campo Grande, Mato Grosso, Brazil. Method: Ten women (median age of 63.4±4.5 years) with little or no pelvic floor dysfunction were subjected to 24 sessions of Pilates exercises lasting one hour each, for 12 weeks. The pressure of the pelvic floor muscles (PFM) was assessed using a perineometer (cmH20) and contractility was assessed with the PERFECT scheme. Data were described as median ± interquartile range and inferential analysis was performed using the Wilcoxon paired test, with a significance level of 5%. Results: In view of the proposed treatment, the degree of voluntary contraction of the PFM of the participants increased from 79.0±83.5 to 90.0±82.0 cmH20, with a statistically significant difference in paired comparison (p=0.012). According to the PERFECT scheme, there was an increase in contraction time (from 5.0±0.1 to 7.0±4.7 seconds) and in the number of fast repetitions (from 7.0±4.5 to 8.0±4.7), with a statistically significant difference for both variables (p=0.017 and p=0.008, respectively). Conclusion: The results indicate that the Pilates method increased the contractility and pressure of the PFM of elderly women with little or no PFM impairment. Further studies are required to determine whether the Pilates method is an effective method for the treatment of women with severe pelvic floor dysfunction.